Relationships between IgE/IgG4 epitopes, structure and function in Anisakis simplex Ani s 5, a member of the SXP/RAL-2 protein family. - María Flor García-Mayoral; Miguel Angel Treviño; Teresa Pérez-Piñar; María Luisa Caballero; Tobias Knaute; Ana Umpierrez; Marta Bruix; Rosa Rodríguez-Pérez (Public Library of Science (PLoS), 2014)
BACKGROUND: Anisakiasis is a re-emerging global disease caused by consumption of raw or lightly cooked fish contaminated with L3 Anisakis larvae. This zoonotic disease is characterized by severe gastrointestinal and/or allergic symptoms which may misdiagnosed as appendicitis, gastric ulcer or other food allergies. The Anisakis allergen Ani s 5 is a protein belonging to the SXP/RAL-2 family; it is detected exclusively in nematodes. Previous studies showed that SXP/RAL-2 proteins are active antigens; however, their structure and function remain unknown. The aim of this study was to elucidate the three-dimensional structure of Ani s 5 and its main IgE and IgG4 binding regions. METHODOLOGY/PRINCIPAL FINDINGS: The tertiary structure of recombinant Ani s 5 in solution was solved by nuclear magnetic resonance. Mg2+, but not Ca2+, binding was determined by band shift using SDS-PAGE. IgE and IgG4 epitopes were elucidated by microarray immunoassay and SPOTs membranes using sera from nine Anisakis allergic patients. The tertiary structure of Ani s 5 is composed of six alpha helices (H), with a Calmodulin like fold. H3 is a long, central helix that organizes the structure, with H1 and H2 packing at its N-terminus and H4 and H5 packing at its C-terminus. The orientation of H6 is undefined. Regarding epitopes recognized by IgE and IgG4 immunoglobulins, the same eleven peptides derived from Ani s 5 were bound by both IgE and IgG4. Peptides 14 (L40-K59), 26 (A76-A95) and 35 (I103-D122) were recognized by three out of nine sera. CONCLUSIONS/SIGNIFICANCE: This is the first reported 3D structure of an Anisakis allergen. Magnesium ion binding and structural resemblance to Calmodulin, suggest some putative functions for SXP/RAL-2 proteins. Furthermore, the IgE/IgG4 binding regions of Ani s 5 were identified as segments localized on its surface. These data will contribute towards a better understanding of the interactions that occur between immunoglobulins and allergens and, in turn, facilitate the design of novel diagnostic tests and immunotherapeutic strategies.